Arnis in Physical Activities Towards Health and Fitness (PATHFit) 3 & 4 Courses: A Deep Dive into Faculty Experiences in Teaching - Peralta, Rovi Gjin P. (Universitas Negeri Semarang (UNNES) in cooperation with ACPES (ASEAN Council of Physical Education and Sport), 2025)
Filipino Martial Arts (FMA), or Arnis, embodies the rich martial heritage of the Philippines, utilizing various weapons for combat and self-defense (Martin et al., 2018). Recognized as the national martial art and sport through Republic Act 9850 in 2009, Arnis has since gained a formal place in education. This study explores faculty experiences teaching Arnis in Physical Activities Towards Health and Fitness (PATHFit) 3 and 4 courses across colleges and universities in Central Luzon (Region III). Employing Colaizzi's 7-step phenomenological technique, with data gathered through interviews and audio-visual recordings, the study uncovers five key themes: (1) The Pedagogical and Cultural Significance of Including Arnis in the Curriculum (2) Enhancing Student Safety and Holistic Development through Arnis (3) Fostering Social Connections, Personal Growth, and Cultural Integration through Arnis (4) Addressing Challenges and Promoting Engagement in Arnis Education and, (5) Enhancing the Teaching and Promotion. Findings revealed that Arnis education transcends physical instruction, fostering cultural pride, resilience, and personal growth among educators and students. Faculty members experienced professional transformation, adopting innovative teaching methods to sustain cultural heritage while addressing modern educational demands. For students, integrating Arnis into PATHFit courses boosted confidence, discipline, and community involvement, strengthening their cultural identity. This study underscores the significance of Arnis as a culturally relevant educational tool that bridges traditional practices with contemporary fitness education. The findings advocate for the development of dynamic, culturally inclusive curricula and faculty training programs, ensuring the sustained relevance of Arnis in academic and societal contexts. By preserving this martial art, educators can inspire both personal development and community cohesion, reinforcing Arnis as a symbol of Filipino identity.